Open-air, low-temperature deposition of phase pure Cu2O thin films as efficient hole-transporting layers for silicon heterojunction solar cells. Issue 29 (14th July 2021) - Nguyen, Van Son; Sekkat, Abderrahime; Bellet, Daniel; Chichignoud, Guy; Kaminski-Cachopo, Anne; Muñoz-Rojas, David; Favre, Wilfried
Abstract : Cu2 O has been integrated as HTL for the first time in SHJs by AP-SALD achieving record power conversion efficiency values. Abstract : Recent research focuses on finding alternative materials and fabrication techniques to replace traditional (p) and (n) doped hydrogenated amorphous silicon (a-Si:H) to reduce cost and boost the efficiency of silicon heterojunction (SHJ) solar cells. In this work, low-cost p-type Cu2 O thin films have been investigated and integrated as a hole-transporting layer (HTL) in SHJ solar cells, using atmospheric-pressure spatial atomic layer deposition (AP-SALD), an open-air, scalable ALD approach. Phase pure Cu2 O thin films have been deposited at temperatures below the degradation limit of the SHJ, thus maintaining the passivation effect of the a-Si:H layer. The effect of deposition temperatures and HTL thicknesses on the performance of the devices has been evaluated. The fabricated Cu2 O HTL-based SHJ cells, having an area of 9 cm 2, reach a power conversion efficiency (PCE) of 13.7%, which is the highest reported efficiency for silicon-based solar cells incorporating a Cu2 O HTL.